Pengaruh Modal Sosial, Fisik Lingkungan, Keuangan Terhadap Pemberdayaan Petani Pasca Pandemi Covid-19 di Kawasan Pesisir Kabupaten Deli Serdang - Nainggolan, Hotden Leonardo; Ginting, Albina; Tabah Trina, Susana (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Nainggolan, H. L., Ginting, A., & Trina, S. T. (2024). The influence of social capital, physical environment, finance on farmer empowerment Post Covid-19 Pandemic in the Coastal Area of Deli Serdang Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 533–542). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Empowerment is one of the important things in increasing community-economic resilience, which is influenced by various factors. This study aimed to determine the effect of social capital, physical capital, financial capital on the empowerment of post pandemic Covid-19 farmers in the coastal area of Deli Serdang Regency. The study was conducted in Deli Serdang Regency as one of the areas affected by Covid-19 in 2020 ago both directly and indirectly. The population in this study was 12,178 farmers' families who were in the coastal area of Percut Sei Tuan Sub-district, the sample in this study was 99 respondents determined by the Slovin formula. The data used in this study are primary data and secondary data. Data are analyzed with multiple linier regression analysis. The results showed that social capital and financial capital had a positive and significant effect on the empowerment of farmers in the coastal area of Deli Serdang Regency, and the physical capital of the environment had a positive but not significant effect on community empowerment in the coastal area of Deli Serdang Regency. Based on the results of research it is recommended that the government empower the community optimally and continuously by utilizing available community resources, such as social capital, financial capital and environmental physical capital in order to increase farmers' income and welfare in coastal areas.